Pseudonectria keratitis-emerging pathogenic fungi in the eye - Yongze Zhu; Peng Nan; Zhongliang Zhu; Youqi Ji; Bingqian Zhuo; Wei Xu; Yumei Ge (BMC, 2024)
Abstract Background Infectious keratitis, a significant contributor to blindness, with fungal keratitis accounting for nearly half of cases, poses a formidable diagnostic and therapeutic challenge due to its delayed clinical presentation, prolonged culture times, and the limited availability of effective antifungal medications. Furthermore, infections caused by rare fungal strains warrant equal attention in the management of this condition. Case presentation A case of fungal keratitis was presented, where corneal scraping material culture yielded pink colonies. Lactophenol cotton blue staining revealed distinctive spore formation consistent with the Fusarium species. Further analysis using Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF MS) identified the causative agent as Fusarium proliferatum. However, definitive diagnosis of Pseudonectria foliicola infection was confirmed through ITS sequencing. The patient's recovery was achieved with a combination therapy of voriconazole eye drops and itraconazole systemic treatment. Conclusion Pseudonectria foliicola is a plant pathogenic bacterium that has never been reported in human infections before. Therefore, ophthalmologists should consider Pseudonectria foliicola as a possible cause of fungal keratitis, as early identification and timely treatment can help improve vision in most eyes.